Optimization of Sugar Reduction using Steviol Glycoside for Ready-to-Drink Sweetened Tea - Mintarsih; Nuri Andarwulan; Dede Robiatul Adawiyah (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Excessive sugar consumption is a major contributor to increased calorie intake and the rising prevalence of obesity, particularly through sweetened ready-to-drink (RTD) teas. This study aimed to optimize formula of reduced sugar RTD tea using steviol glycoside as sweetener, in combination with maltodextrin and xanthan gum, through a mixture design approach. Steviol glycoside next called as stevia is a zero-calorie natural sweetener with a sweetness intensity approximately 300 times of sucrose. Maltodextrin was employed as filler, while xanthan gum was added to improve mouthfeel. The optimized formulation achieved a 2% reduction in sugar content using 0.009% stevia, 0.029% xanthan gum, and 1.962% maltodextrin. A reference product was formulated based on the most popular RTD jasmine black tea in the Indonesian market, which contains 7.7% (b/v) sugar per 100 mL. Result of spectrum descriptive analysis (SDA) sensory evaluation, conducted before and after ultra-high temperature (UHT) processing, showed no significant differences in sweetness, mouthfeel, astringency and jasmine aroma attributes. Compare to reference, in 100 mL product, sugar content was reduced from 7.68 to 5.78%, while total calorie slightly decreased from 30.71 to 30.13 kcal. In addition, the cost is slightly more expensive by IDR 126 per 350 mL package.